2022
DOI: 10.1038/s41531-022-00438-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired migratory phenotype of CD4+ T cells in Parkinson’s disease

Abstract: Dysfunctions in the immune system appear implicated in both disease onset and progression of Parkinson’s disease (PD). Neurodegeneration observed in the brain of PD patients has been associated with neuroinflammation that is linked to alterations in peripheral adaptive immunity, where CD4+ T cells are key players. In the present study, we elucidated the immunological aspect of PD by employing a wide range of cellular assays, immunocytochemistry and flow cytometry to examine CD4+ T cells. We particularly invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Recent research indicates that overexpression of α-synuclein protein in the midbrain of mice leads to upregulation of major histocompatibility complex class II (MHCII) proteins on CNS bone marrow cells, as well as in ltration of CD8 + and CD4 + T cells releasing IFNγ into the CN (Williams et al, 2021). Furthermore, a study examining the relationship between PD patients and neuroin ammation demonstrated severe impairment in the functionality of peripheral blood CD4 + T cells in PD (Mamula et al, 2022). In another study, in comparison with PD patients with normal cognitive characteristics, those with cognitive impairment exhibited a higher quantity of circulating lymphocytes (Magistrelli et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Recent research indicates that overexpression of α-synuclein protein in the midbrain of mice leads to upregulation of major histocompatibility complex class II (MHCII) proteins on CNS bone marrow cells, as well as in ltration of CD8 + and CD4 + T cells releasing IFNγ into the CN (Williams et al, 2021). Furthermore, a study examining the relationship between PD patients and neuroin ammation demonstrated severe impairment in the functionality of peripheral blood CD4 + T cells in PD (Mamula et al, 2022). In another study, in comparison with PD patients with normal cognitive characteristics, those with cognitive impairment exhibited a higher quantity of circulating lymphocytes (Magistrelli et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Other research suggests an overall decrease in circulating lymphocytes with increased Th1 and Th17 but decreased Th2 and regulatory T lymphocytes [ 45 ] or no changes in Th1 and Th2 subsets but an increase in the Th17 lymphocyte population [ 46 ]. In addition to differences in population sizes and ratios, functional studies indicate alterations in lymphocyte populations in PD, including deficits in migratory capacity of CD4+ T lymphocytes from PD patients [ 47 ] and impaired suppressor functions of T regulatory cells in PD, which could be restored by ex vivo expansion [ 41 ]. A third study reported that PD disease severity was associated with higher activation levels of T lymphocytes in response to phytohemagglutinin stimulation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of CD4 T-cell migration for the neuroinflammatory response in PD, it has been observed through in vitro studies that these lymphocytes from PD patients are slower and less viable than those from healthy control groups, mainly due to alterations in mitochondrial positioning and organelle activity—particularly in the study from Mamula et al They reported alterations in mitochondrial positioning coexisting with a statistically significant decrease in ROS in CD4 T cells from PD patients, which, according to their view, is associated with the poor immune response observed as one of the clinical characteristics of some PD patients. However, the evidence of their in vitro model should be analyzed with caution since this does not rule out the increased production of ROS in brain tissue as an important factor in the development and progression of PD [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%